In Situ Single-Molecule AFM Investigation of Surface-Induced Fibrinogen Unfolding on Graphite - Dubrovin, Evgeniy V (Langmuir : the ACS journal of surfaces and colloids, 2019)
Fibrinogen adsorption plays a key role in important biological processes, such as blood coagulation and foreign body reaction, which determine the biocompatibility of a material. Fibrinogen conformation on a surface is one of the main factors triggering these processes. Understanding the conformational dynamics of fibrinogen molecules adsorbed on solid surfaces is, therefore, of great interest in biomedicine and may contribute to the development of new biomaterials. In this work, unfolding of fibrinogen molecules adsorbed on a model surface (highly oriented pyrolytic graphite modified with an oligoglycine-hydrocarbon graphite modifier) is directly visualized using time-lapse atomic force microscopy. A gradual transformation of native-like fibrinogen molecules into fibrillar structures is observed at a timescale of several minutes. This transformation is accompanied by a decrease in molecular height from 4-5 to 1-2 nm. Independent unfolding of different fibrinogen domains is demonstrated. The obtained results provide a new, direct insight into the unfolding of individual fibrinogen molecules on a surface and give new opportunities for the development of graphite-based biosensors and biomaterials